VEGF sticky‐trap: the first report of a non‐systemically acting angiogenesis inhibitor. Issue 5 (May 2014) - Favara, David M; Harris, Adrian L
<x xml:space="preserve">Abstract</x> Current therapeutic anti‐angiogenic biologics used for the treatment of pathological ocular angiogenesis such as in diabetic retinopathy and wet macular degeneration often lead to detrimental side effects due to their interference with normal blood vessel physiology. In this issue of EMBO Molecular Medicine, Michael et al report on a novel angiogenesis inhibitor with unique properties that allow for local inhibition of angiogenesis without detectable systemic side effects.